EMBRYONIC AND EARLY LARVAL DEVELOPMENT OF WHITESPOTTED GREENLING HEXAGRAMMOS STELLERI (SCORPAENIFORMES: HEXAGRAMMIDAE) FROM THE NORTHERN OKHOTSK SEA - R. R. Yusupov; R. R. Yusupov (Известия ТИНРО)
In vitro morphological development of whitespotted greenling Hexagrammos stelleri from the northern Okhotsk Sea is described in detail and illustrated from the eggs fertilization to the larvae transition to exogenous feeding. Mean diameter of the fertilized eggs is determined as 2.03 mm (1.80–2.30 mm). The embryos hatch in 30 days and 6 hours after fertilization of eggs under the water temperature of 7.1–12.4 оC (on average 11.5 оC). The hatched prelarvae have the size TL 7.73–9.20 mm (on average 8.49 ± 0.09 mm) and SL 7.48–8.80 (8.15 ± 0.08 mm).